2009
DOI: 10.1590/s0066-782x2009000100007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência do hiperaldosteronismo primário em uma liga de hipertensão arterial sistêmica

Abstract: The prevalence of primary hyperaldosteronism in the studied sample was 0.96% of the total. However, when only the patients with refractory hypertension were evaluated, the prevalence was 14.3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
3
0
5
Order By: Relevance
“…As already mentioned, several cross-sectional and prospective studies in unselected hypertensive populations have shown that the prevalence of PA is much higher than previously believed, although it varies significantly between studies ranging from 4.6 to 16.6% when confirmatory tests to diagnose PA were used (Table 2) (5,6,7,8,21,71,75,76,77,78,79,80,81,82). However, in patients with resistant hypertension, the prevalence of PA is reported to be even higher ranging from 17 to 23% (16,83).…”
Section: Prevalence Of Pa In Hypertension and Pre-hypertensionmentioning
confidence: 93%
“…As already mentioned, several cross-sectional and prospective studies in unselected hypertensive populations have shown that the prevalence of PA is much higher than previously believed, although it varies significantly between studies ranging from 4.6 to 16.6% when confirmatory tests to diagnose PA were used (Table 2) (5,6,7,8,21,71,75,76,77,78,79,80,81,82). However, in patients with resistant hypertension, the prevalence of PA is reported to be even higher ranging from 17 to 23% (16,83).…”
Section: Prevalence Of Pa In Hypertension and Pre-hypertensionmentioning
confidence: 93%
“…Связь между избыточным потреблением поваренной соли и повышением артериально го давления была замечена задолго до откры тия методов измерения артериального дав ления и появления понятия «артериальная гипертензия». Сочетание наследственной пред расположенности к гипертонической болезни и Читайте нас на сайте: http://med expert.com.ua избыточному потреблению соли приводит к тому, что компенсаторные почечные механизмы со вре менем уже не могут полностью выводить избыток соли, что в свою очередь приводит к увеличению объема жидкости, вследствие чего увеличивается объем циркулирующей крови и повышается арте риальное давление [18,20]. В нашем исследовании большинство детей с АГ, страдавших избыточным весом и ожирением, питались несбалансировано.…”
Section: Discussionunclassified
“…Другое исследо вание [3] выявило положительную корреля цию между артериальным давлением, индек сом массы тела (ИМТ) и количеством потреб ляемой соли. Исследования последних лет доказали, что более восприимчивыми к разви тию АГ при повышеном потреблении натрия являются пациенты с ожирением, лица африканского происхождения, а также лица с отягощенным семейным анамнезом по АГ [4,13,18,20]. Синергическое дейстие вышепере численых факторов увеличивают риск разви тия АГ у детей.…”
unclassified
“…The reported prevalence of PA in the general hypertensive population varies widely, ranging from 1% to 29.8%. [3][4][5][6] A systematic review data showed greatly variable prevalence and high heterogeneity between studies. 7 The heterogeneous results of these studies have been associated with geographic differences, patient selection, healthcare setting and variability in screening tests and diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of secondary hypertension is primary aldosteronism (PA). The reported prevalence of PA in the general hypertensive population varies widely, ranging from 1% to 29.8% 36. A systematic review data showed greatly variable prevalence and high heterogeneity between studies 7.…”
Section: Introductionmentioning
confidence: 99%